Assessment of Drinking Water Quality from Bottled Water Coolers. - Marzieh Farhadkhani; Mahnaz Nikaeen; Behrouz Akbari Adergani; Maryam Hatamzadeh; Bibi Fatemeh Nabavi; Akbar Hassanzadeh (Tehran University of Medical Sciences, 2014)
Drinking water quality can be deteriorated by microbial and toxic chemicals during transport, storage and handling before using by the consumer. This study was conducted to evaluate the microbial and physicochemical quality of drinking water from bottled water coolers.A total of 64 water samples, over a 5-month period in 2012-2013, were collected from free standing bottled water coolers and water taps in Isfahan. Water samples were analyzed for heterotrophic plate count (HPC), temperature, pH, residual chlorine, turbidity, electrical conductivity (EC) and total organic carbon (TOC). Identification of predominant bacteria was also performed by sequence analysis of 16S rDNA.The mean HPC of water coolers was determined at 38864 CFU/ml which exceeded the acceptable level for drinking water in 62% of analyzed samples. The HPC from the water coolers was also found to be significantly (P < 0.05) higher than that of the tap waters. The statistical analysis showed no significant difference between the values of pH, EC, turbidity and TOC in water coolers and tap waters. According to sequence analysis eleven species of bacteria were identified.A high HPC is indicative of microbial water quality deterioration in water coolers. The presence of some opportunistic pathogens in water coolers, furthermore, is a concern from a public health point of view. The results highlight the importance of a periodic disinfection procedure and monitoring system for water coolers in order to keep the level of microbial contamination under control.